Scale dependence of energy transfer in turbulent plasma. Issue 4 (3rd November 2018) - Yang, Yan; Wan, Minping; Matthaeus, William H; Sorriso-Valvo, Luca; Parashar, Tulasi N; Lu, Quanming; Shi, Yipeng; Chen, Shiyi
ABSTRACT: In the context of space and astrophysical plasma turbulence and particle heating, several vocabularies emerge for estimating turbulent energy dissipation rate, including Kolmogorov–Yaglom third-order law and, in its various forms, j· E (work done by the electromagnetic field on particles), and -(P · ) · u (pressure–strain interaction), to name a couple. It is now understood that these energy transfer channels, to some extent, are correlated with coherent structures. In particular, we find that different energy dissipation proxies, although not point-wise correlated, are concentrated in proximity to each other, for which they decorrelate in a few ion inertial scales. However, the energy dissipation proxies dominate at different scales. For example, there is an inertial range over which the third-order law is meaningful. Contributions from scale bands stemming from scale-dependent spatial filtering show that the energy exchange through j· E mainly results from large scales, while the energy conversion from fluid flow to internal through -(P · ) · u dominates at small scales.